Pendidikan Etika Agama Hindu Bagi Siswa Adi Widya Pasraman Sutasoma - Ismawati, Ika; Jatiyasa, I Wayan (Metta : Jurnal Ilmu Multidisiplin, 2025)
Moral degradation has become a widespread discourse among society, especially the Hindu community in Nabire district, Papua. The development of information technology has coused the formation of nomophobia syndrome in Hindu children in Papua. This occurs because children are starting to get to know smartphones after a long time behind technology. Children are starting to become addicted and can not be separated from smartphones, this is indicated by the habit of children always carrying smartphones both in class and outside of class. This condition is certainly very worrying for the development of the Hindu generation in Nabire district, Papua. Therefore, the teaching staff at Adi Widya Prasaman Sutosoma began to innovate to overcome this phenomenon, namely by providing education on Hindu religious ethics to students. The problem discussed is the learning strategy for Hindu religious ethics education in Adi Widya Pasraman Sutosoma, Nabire dictrict. This research aims to determine the Hindu religious ethnics learning activities at Adi Widya Pasraman Sutosoma. Data was obtained from observations, interviews and document studies using purposive sampling as a technique for determining informants. The collected data was analyzed using qualitative analysis techniques. This research uses the Behavioristic Theory and Sociological Theory methods. Based on the results of the anlysis carried out, it shows that the learning strategy for Hindu religious ethics education applies a group strategy, considering that this learning focuses more on guidance on ethics and morality, then the approach used is a religious approach because the scope of the material refers to Hindu religious teachings. The method used to deliver material, teaching staff uses lecture and discussion methods.